Assessment Instrument for Early Numeracy Skills in Young Children - Amalia Husna; Elvira Khori Ulni; Harlina Ramelan; Imam Muthie; Wulan Rahmadia Novera; Jamilah Mohd Basir (Jurnal Pendidikan Anak Usia Dini Undiksha, 2025)
Early numeracy skills serve as a crucial foundation for children's academic readiness and success at subsequent levels. However, the availability of assessment instruments that are appropriate to the developmental characteristics of early childhood and possess adequate psychometric qualities is still limited. This study aims to analyze and validate the quality of early numeracy skills assessment instruments in early childhood. The study employed a research and development approach, involving early childhood as test subjects. Data were collected through literature review, observation, interviews, expert validation, and instrument trials. Instrument quality was analyzed through content validity, empirical validity, and internal reliability testing to ensure measurement consistency and accuracy. The results showed that the developed instrument had a high level of content validity, supported by good inter-item consistency and strong internal reliability. These findings confirm that the instrument is suitable for comprehensive and systematic investigation of early numeracy skills. Implications: This instrument can be used by educators as a basis for designing learning strategies that are more adaptive and responsive to the numeracy development needs of early childhood.